Child graves at Galayeri settlement of the Leilatepe culture - Museibli, Najaf (Revista Arheologică, 2025)
In the 1980s, the archaeological culture of the same name was discovered in the Karabakh region of Azerbaijan during excavations of the Chalcolithic settlement of Leilatepe. Since the early 21st century, thanks to the expansion of archaeological explorations, numerous settlements and tombs belonging to the Leilatepe culture have been discovered in the western region of the Republic of Azerbaijan, in Karabakh, Mughan and Gabala, and extensive excavations have been carried out in many of them. It has been established that the Leilatepe culture emerged in the Late Chalcolithic period, end of the 5th millennium BC – beginning of the 4th millennium BC as a result of mass migrations from Eastern Anatolia and Northern Mesopotamia to the South Caucasus. This culture lasted until the mid of the 4th millennium BC. With some exceptions, monuments belonging to this culture were mainly discovered in the territory of Azerbaijan. As a result of continued migrations from the Leilatepe culture area to the North Caucasus, the Maikop culture with the same ceramic traditions was formed there. Among the main indicators of the Leilatepe culture, the use of the potter’s wheel in ceramic production and the infant burials in various types of pottery vessels can be especially noted. One of the most extensively excavated monuments belonging to this culture is the Galayeri settlement. The richest finds of the Leilatepe culture were discovered precisely in Galayeri. In all the monuments where extensive excavations were carried out related to this culture, child graves in pottery vessels were discovered. Such graves of the monuments belonging to the Leilatepe culture were mostly found in Galayeri.
Keywords: Azerbaijan; Chalcolithic period; migrations; Leilatepe culture; Galayeri settlement; hild graves; burial vessels; burial customs